Innovative Global Health Care Experiences for Nursing Students: Microsemesters and Internships. Issue 5 (September 2019) - Graber, Jennifer S.; Saylor, Jennifer; Johnson, Amy N.
Abstract : Abstract: Global experiential learning using clinical internships and microsemesters is expanding in nursing as an alternative to full-semester study abroad. When incorporated into the curriculum, students have a broader perspective on global health care issues. For example, students learn historic and cultural concepts that are uniquely Australian while studying diversity in a condensed two-week microsemester. We describe the development and incorporation of global internships and alternative global experiences for undergraduate nursing students.